Preparation of microspheres containing low solubility drug compound by electrohydrodynamic spraying. - Bohr, A; Kristensen, J; Stride, E; Dyas, M; Edirisinghe, M (2011)
Micro- and nanoparticle formulations are widely used to improve the bioavailability of low solubility drugs. In this study, electrospraying is introduced as a method for producing drug-loaded microspheres at ambient conditions. PLGA microspheres containing celecoxib, a low solubility drug, were prepared with the objective of producing near-monodisperse microspheres with the drug in a stable amorphous form. We found that it is possible to produce near-monodisperse celecoxib-loaded PLGA microspheres at different polymer:drug ratios. The microspheres produced were in the size range 1-5 μm depending on the polymer:drug ratio and had smooth surfaces. Thermal analysis further indicates that celecoxib is present in an amorphous form inside the microspheres. Drug dissolution studies showed an initial burst release followed by a period of sustained release with the dissolution curve depending on the polymer:drug ratio. Electrospraying is thus a promising method for producing amorphous microspheres of low solubility drugs such as celecoxib. The microsphere properties may be further optimized to achieve an appropriate dissolution profile with the aim of increasing oral bioavailability of low solubility drugs.